Simulation of Cake Filtration for Polydisperse Particles. Issue 3 (March 2016) - Becker, Jürgen; Cheng, Liping; Kronsbein, Cornelia; Wiegmann, Andreas
Abstract: When simulating the buildup of a filter cake consisting of polydisperse particles, the choice of the numerical resolution is difficult as particles may cover a large range of diameters. A method was developed that allows to model cake filtration at any resolution. Resolution‐dependent fitting parameters can be found such that the solidity and resistivity of the resulting filter cake will be independent of the chosen resolution. The cake buildup is simulated on the filter media scale. Flow through the porous parts is modeled with the Stokes‐Brinkman equation, which requires the local solidity and flow resistivity of each porous grid cell as input. It is described how to set the local solidity and resistivity such that a given global solidity and flow resistivity of the filter cake is achieved and the simulated pressure drop is independent of the chosen resolution. Abstract : The choice of numerical resolution is difficult for simulating the buildup of a filter cake consisting of polydisperse particles with widely ranging diameters. A method is proposed allowing to model cake filtration at any resolution. The cake buildup is simulated on the filter media scale. The found parameter values may be applied to model cake filtration correctly for any structure model.